2014
DOI: 10.1016/j.vhri.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Health Facility Cost of Buruli Ulcer Wound Treatment in Ghana: A Case Study

Abstract: The cost of BU wound treatment takes a considerable amount of the hospital's expenditure. This shows the importance of health facility cost as one of the decision-making tools for both resource allocation and mobilization. Hospital management must therefore constantly examine its staffing norms and the associated cost to improve the hospital's resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Even with effective antimicrobial therapy, BU wound healing is slow, often requiring many months of care 6 . Studies from Ghana and Nigeria have reported that BU imposes substantial costs on affected individuals, their households 7,8 , and the health system 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Even with effective antimicrobial therapy, BU wound healing is slow, often requiring many months of care 6 . Studies from Ghana and Nigeria have reported that BU imposes substantial costs on affected individuals, their households 7,8 , and the health system 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Two of the studies are population based [4,5], providing the first information on the economic burden of substance abuse and several types of cancers in the Russian Federation. Other studies estimated the COI in a sample of patients with rheumatoid arthritis and its relation to disease severity [6]; the cost related to work productivity of patients with ankylosing spondylitis, rheumatoid arthritis, and psoriasis in the Czech Republic [7]; the direct cost of HIV-infected patients in Greece [8]; and a single-center study from Ghana assessing the health facility cost of Buruli ulcer wound infection [9]. Although all these studies present a cost analysis, some may not be considered traditional COI analyses because of their narrow scope.…”
mentioning
confidence: 99%
“…This disease is characterized by the progression of painless nodules, papules, plaques or edemas to painless ulcers, mainly on arms and legs ( 9 ). The painlessness of the disease may be attributed to the effect of mycolactone on specific neurological pathways of the host ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The painlessness of the disease may be attributed to the effect of mycolactone on specific neurological pathways of the host ( 10 ). These ulcers can lead to potential disfigurement or long-term disability if the patient is not treated timeously ( 8 , 9 ). The recommended treatment consists of 10 mg/kg of rifampicin once daily and 7.5 mg/kg of clarithromycin twice daily ( 1 ).…”
Section: Introductionmentioning
confidence: 99%